Acceleration and deceleration of convoy electrons in grazing-ion-surface collisions. - Gravielle, Maria Silvia (2003)
Convoy-electron emission produced by grazing-ion–surface scattering is studied in the framework of the distorted-wave theory. We develop a model, here named field distorted-wave (FDW) approximation, to describe the effect of the surface interaction on the electronic transition. In the model, the action of the surface field on the ejected electron is seen as an additional momentum transfer that depends on the projectile position. We apply the FDW approximation to analyze electron distributions for 100 keV protons impinging on LiF(100) and Al(111) surfaces, which are insulator and metal materials, respectively. In the case of metals, the dynamic screening of the projectile is included in the Jost function corresponding to the final state. As experimentally observed, energy spectra of forward-ejected electrons display a prominent structure associated with the convoy-electron emission. We find that the maximum of the convoy-electron distribution is decelerated for LiF and accelerated for Al, with respect to its position in ion-atom collisions, in quantitative agreement with the experimental data.